Praktik Mom Shaming Oleh Netizen Indonesia Terhadap Selebritis Yang Melakukan Sharenting Di Media Sosial - Annisa Savira (Airlangga University, 2020)
This research focuses on analyzing the practice of shaming mothers that occurred on the Instagram accounts of two celebrity mothers, Andien Aisyah and Rachel Vennya. Researchers raised this topic because mom shaming is a phenomenon that often occurs nowadays, but not many have conducted an in-depth investigation of mom shaming so that it affects knowledge and awareness of mom shaming's actions and the impact of mom shaming on a mother. Analysis of the practice of mom shaming is carried out using the textual analysis method, where the researcher interprets the text from the sharenting practices of celebrity mothers on their social media, mom shaming comments by Indonesian netizens in the comments column of their uploads, and also resolutions or feeds. The results of this study indicate that mom shaming is often accepted by celebrity mothers, in this case Andien Aisyah and Rachel Vennya, regardless of the parenting method applied. However, there are differences in mom shaming patterns from sharenting practices or how celebrity mothers are free from parenting on their social media pages regarding the persona of the celebrity mother. The results of this study also show the intention of giving mom shaming text by Indonesian netizens to celebrity mother, where the messages are mom shaming messages that express their thoughts and feelings on their social media pages.